Visual presentation of settlement complexes from the early Iron Age from Milejowice, site 19, and selected problems of 3D modelling in archaeology - Małgorzata Markiewicz (Przegląd Archeologiczny, 2019)
Archaeological excavations in Milejowice, Wrocław district, were carried out in 1999-2002 in connection with the modernization of the A-4 motorway. During those excavations, relics of a settlement from the early Iron Age were discovered that were distinguished by the layout of the buildings. The visual presentation in the form of a 3D reconstruction of the Hallstatt settlement from Milejowice is a computer created image based on analysis of the sources obtained duringexcavation work. The purpose of 3D imaging of the features discovered on site was to provide a spatial representation of the settlement’s buildings, divided into individual phases. An analysis of the development and spatial organization of the settlement complexes discovered at site No. 19 in Milejowice, was carried out by Jarosław Kopiasz from the Archaeological Museum in Biskupin. For spatial reconstruction, one of many possible suggestions for interpreting the buildings of this settlement was selected. In the 3D technique six separate settlement zones were reconstructed at this site, along with the individual phases of their functioning. The visual presentation of settlement complexes discovered at the Milejowice site is a valuable source of information on early Iron Age construction. The visualization verified the collected data, and 3D modelling facilitated the interpretation of the research results. With the help of Computer Aided Design (CAD) and three-dimensional modelling, it was possible to analyze the spatial organization of settlement complexes from Milejowice and to separate the individual phases of development of the designated zones. It should be noted, however, that digital reconstructions of settlement complexes from Milejowice remain the hypothesis of researchers, based on their analysis of documentation and theoretical assumptions. KEY WORDS: visualization, 3D reconstruction, early Iron Age, Milejowice